Implementation Internal Educational Supervision Increase Competence Teacher Pedagogy at Public Elementary School 60 Palembang - Eva Yuli Nirvana; Meilia Rosani; Muhammad Fahmi (International Journal of Educational Evaluation and Policy Analysis, 2025)
This research aims to examine the planning, implementation, and follow-up of the principal's supervision at SD Negeri 60 Palembang in improving teacher professionalism. The focus of the research includes how the supervision planning is carried out, the implementation applied, and the forms of follow-up that contribute to the development of teacher professionalism at the school. This research is a qualitative study using ethnographic research methods because the study was conducted in a natural setting. The results of the research at SD Negeri 60 Palembang show that educational supervision is conducted according to management, with an approach of open discussion and constructive feedback principles. Although constrained by limited resources, teachers and the school investigated it creatively. The evaluation shows the implementation of directed supervision, with realistic follow-up plans and individual initiatives as strengths in improving the quality of education. Research results at SD Negeri 60 Palembang indicate that educational supervision is conducted according to management principles, with an approach of open discussion and constructive feedback. Although constrained by limited resources, teachers and the school investigated it creatively. The evaluation shows the implementation of directed supervision, with realistic follow-up plans and individual initiatives as strengths in improving the quality of education.